Amplitude and timing of somatosensory cortex activity in Task Specific Focal Hand Dystonia - Dolberg, Rebecca (2011)
OBJECTIVE: Task-specific focal hand dystonia (tspFHD) is a movement disorder diagnosed in individuals performing repetitive hand behaviors. The extent to which processing anomalies in primary sensory cortex extend to other regions or across the two hemispheres is presently unclear. METHODS: In response to low/high rate and novel tactile stimuli on the affected and unaffected hands, magnetoencephalography (MEG) was used to elaborate activity timing and amplitude in the primary somatosensory (S1) and secondary somatosensory/parietal ventral (S2/PV) cortices. MEG and clinical performance measures were collected from thirteen patients and matched controls. RESULTS: Compared to controls, subjects with tspFHD had increased response amplitude in S2/PV bilaterally in response to high rate and novel stimuli. Subjects with tspFHD also showed increased response latency (low rate, novel) of the affected digits in contralateral S1. For high rate, subjects with tspFHD showed increased response latency in ipsilateral S1 and S2/PV bilaterally. Activation differences correlated with functional sensory deficits (predicting a latency shift in S1), motor speed and muscle strength. CONCLUSIONS: There are objective differences in the amplitude and timing of activity for both hands across contralateral and ipsilateral somatosensory cortex in patients with tspFHD. SIGNIFICANCE: Knowledge of cortical processing abnormalities across S1 and S2/PV in dystonia should be applied towards the development of learning based sensorimotor interventions.